IBM z13 and IBM z13s technical introduction - White, Bill; De Leon, Cecilia A.; Hoogerbrug, Edzard; Palacio, Ewerson; Pinto, Franco; Sannerud, Barbara; Soelig, Martin; Troy, John; Yang, Jin J. (IBM Corporation, International Technical Support Organization, 2016)
This IBM® Redbooks® publication introduces the latest IBM z Systems™ platforms, the IBM z13™ and IBM z13s. It includes information about the z Systems environment and how it can help integrate data, transactions, and insight for faster and more accurate business decisions. The z13 and z13s are state-of-the-art data and transaction systems that deliver advanced capabilities that are vital to modern IT infrastructures. These capabilities include: Accelerated data and transaction serving Integrated analytics Access to the API economy Agile development and operations Efficient, scalable, and secure cloud services End-to-end security for data and transactions This book explains how these systems use both new innovations and traditional z Systems strengths to satisfy growing demand for cloud, analytics, and mobile applications. With one of these z Systems platforms as the base, applications can run in a trusted, reliable, and secure environment that both improves operations and lessens business risk.
"SG24-8250-01.". - "This edition applies to the following IBM z Systems platforms: IBM z13 and z13s.". - Description based on online resource; title from title page (viewed March 28, 2016)
Keywords: z/OS; Storage area networks (Computer networks); Computer network architectures; Information storage and retrieval systems; IBM computers -- Programming; Information Systems; Réseaux de stockage (Informatique); Réseaux d'ordinateurs; Architectures; Systèmes d'information; IBM (Ordinateurs); Programmation; IBM computers; Programming